Influences of harvester and weather conditions on field loss and milling quality of rough rice - Khir, Ragab; Atungulu, Griffiths; Chao, Ding; Pan, Zhongli (International Journal of Agricultural and Biological Engineering, 2017)
A better understanding of factors affecting field losses and milling quality during harvest is needed to improve the economic value of rice. The main objective of this study was to evaluate the impact of harvester header, harvester type, and weather conditions on field loss and milling quality of rough rice. Four popular harvesters equipped with different headers: John Deere 9870 with header D60-S, John Deere 9860 with header D972-S, Hardy, and John Deere 9770 with stripper header were evaluated in this study. The header and total field losses of rice were evaluated for each harvester under regular, rainy and windy weather conditions. Tests were conducted in a rice field cultivated with medium grain rice, variety M206, at Grimes, CA. Total rice yield (TRY), head rice yield (HRY) and whiteness index (WI) were examined to evaluate the effect of weather conditions on milling quality. The obtained results revealed that the rice field loss was affected by harvester header and type, and weather conditions. Among the conventional headers, D60-S significantly reduced the rice loss compared to the D972-S and the Hardy. Harvesting with John Deere 9860 resulted in significant header and field loss compared to other tested harvesters. The average loss increased from 236.2 kg/hm2 and 445.2 kg/hm2 under regular condition to 711.1 kg/hm2 and 907.9 kg/hm2 under windy condition for John Deere 9870 and John Deere 9860, respectively. The corresponding loss percentages increased from 2.6% and 4.9% to 7.9% and 10.1%. HRY was significantly affected by weather condition at harvest time. However, the weather condition had no significant effect on TRY and WI. To minimize the rice field loss and obtain good milling quality, commercial rice harvesting during regular weather conditions is important. A proper combination of harvester type and header could be vital for reducing the rice loss.Keywords: rice, harvesters, field loss, weather conditions, milling quality, harvester headerDOI: 10.25165/j.ijabe.20171004.2993Citation: Khir R, Atungulu G, Ding C, Pan Z L. Influences of harvester and weather conditions on field loss and milling quality of rough rice. Int J Agric & Biol Eng, 2017; 10(4): 216–223.